Understanding acceptance of shared autonomous vehicles among people with different mobility and communication needs. (October 2022) - Miller, Kristine; Chng, Samuel; Cheah, Lynette
Highlights: People with different mobility needs are surveyed and interviewed regarding shared AVs in public transport. Majority are anticipating shared AVs with positive attitudes and emotions. AV service safety and reliability are ranked as top concerns. Visually impaired and hard of hearing users wanted 'live' intercom, and auditory and visual cues. Inclusive experiential rides on AVs can aid wider acceptance. Abstract: Most studies of autonomous vehicle (AV) acceptance have focused on its acceptance by the general population. There is a dearth of knowledge among users with different abilities and needs. Hence, this study addresses this gap by investigating user acceptance of shared AVs among people with different mobility and communication needs in Singapore. Understanding the perspectives of these users is critical to ensure that shared AVs services are inclusive, aiding in acceptance. The groups studied are the 1) blind and visually impaired; 2) deaf and hard of hearing; 3) individuals using mobility aids, such as wheelchair, scooter, or cane; 4) individuals with autism and their caregivers; 5) families with young children and pregnant women; 6) seniors (age 60 + ). Using an online survey (n = 300) and focus group discussions (n = 53), we found that these user groups are (i) anticipating AV in public transport with positive attitudes and emotions, and (ii) generally concerned about various aspects of safety. AV service safety and reliability are ranked as top concerns across all groups surveyed. Users who are likely to require onboard assistance prioritised ease of boarding and alighting, and all groups ranked the presence of 'onboard service staff' as less important. Participants identified several important service features, such as onboard safety features - especially a 'live' intercom, and auditory and visual cues for visually impaired and hard of hearing. Some users would also like dedicated lanes for AVs. Inclusive experiential rides on an AV will help members of these groups feel more comfortable and prepared for AVs once deployed.